Research Progress of Myocardial Fibrosis and Atrial Fibrillation - Li, Guangling; Yang, Jing; Zhang, Demei; Wang, Xiaomei; Han, Jingjing; Guo, Xueya (Frontiers in Cardiovascular Medicine, 2022)
Abstract：With the aging population and the increasing incidence of basic illness such as hypertension and diabetes (DM), the incidence of atrial fibrillation (AF) has increased significantly. Atrial fibrillation is the most common arrhythmia in clinical practice, which can cause heart failure (HF) and ischemic stroke, increasing disability and mortality. Current studies point out that myocardial fibrosis is one of the most critical substrates for the occurrence and maintenance of atrial fibrillation. Although myocardial biopsy is the gold standard for evaluating myocardial fibrosis, it is rarely used in clinical practice because it is an invasive procedure. The accuracy of serological markers in evaluating myocardial fibrosis is controversial. At the same time, anti-myocardial fibrosis therapy is expected to inhibit the occurrence and maintenance of atrial fibrillation. This review focuses on the pathogenesis of myocardial fibrosis, serological evaluation, imaging evaluation, anti-fibrosis treatment to discuss the existing problems, to provide new ideas for the evaluation and treatment of myocardial fibrosis, and to reduce atrial fibrillation burden further.